Understanding the barriers and knowledge gaps to climate-smart agriculture and climate information services: A multi-stakeholder analysis of smallholder farmers’ uptake in Ghana - Philip Antwi-Agyei; Frank Baffour-Ata; Joseph Alhassan; Felix Kpenekuu; Andrew J. Dougill (World Development Sustainability)
The uptake of climate-smart agriculture (CSA) and climate information services (CIS) among Ghanaian smallholder farmers remains low despite their promise to address climate change risks. Yet, research on the barriers and knowledge gaps that prevent smallholder farmers from widely adopting CSA and CIS remains limited. This study explores the perspectives of multiple stakeholders on the key barriers and knowledge gaps impeding the successful uptake of CSA and CIS among smallholders in Ghana. Data were obtained from participatory research methods including national (n = 56) and regional (n = 47) stakeholder workshops and interviews. Data were transcribed and thematically analyzed. Results show that various intersecting barriers relating to funding, sociocultural, political, climate data and information, human resources, environment, and infrastructure hinder smallholders' uptake of CSA and CIS in Ghana. Results further reveal that uptake is hampered by some knowledge gaps, stemming mainly from the policies and their implementation approaches, capacity building, and empirical evidence of CSA technologies. Smallholders' uptake of CSA and CIS could be improved by designing appropriate interventions relating to financial and human resources, climate data and information, environmental regulations, and capacity building. These findings demonstrate the need for the government, non-governmental organizations, researchers, and community leaders to support CSA and CIS uptake in Ghana.